2035 Vision: Doubling the Value Added of Finland´s Forest sector - Lintunen, Jussi; Kohl, Johanna; Buchert, Johanna; Asikainen, Antti; Jyske, Tuula; Maunuksela, Jyri; Lehto, Jani (Luonnonvarakeskus, 2024)
The forest sector plays a significant role in Finland’s national economy. Finland and other Nordic countries have very high-quality forest sector research and innovation activities. Finland’s bioeconomy strategy has set the goal of doubling the value added of the bioeconomy. In this discussion paper, we examine the opportunity to achieve of the objectives of Finland’s bioeconomy strategy in terms of increasing the value added of the forest sector. The forest sector’s research has created and is creating highly potential wood biomass innovations on an industrial scale. At the moment, the value added of Finland’s forest bioeconomy is created at the beginning of the value chain. To advance our position in this chain, also national investments are needed. In this study, we focus on the value added of pulp fiber, the mechanical wood product industry, and the further processing of their by-products. We present two scenarios in which the forest sector achieves the €50 billion value added target set in the Finnish bioeconomy strategy by 2035 for its part. This study concentrates on economic variables, factors such as biodiversity or carbon sink impacts, which play a crucial role in the real-world future prospects and targeting of measures in the forest sector, are not assessed. For the pulp industry, we examine the conversion of pulp fiber into textile fiber and the further processing of lignin, extracted as a by-product of cooking, into a concrete plasticizer. We also examine the growing production of new types of packaging materials that replace plastics. These products were selected as examples for our review because sufficient information was available for value added calculations. Our review shows that significant value appreciation can already be achieved by refining pulp into textile fiber, but there would be much greater potential in moving further up the value chain to textile materials and consumer products. There is great potential in further processing the by-product lignin, and in this work we assume it is utilized as a concrete plasticizer with relatively high value added, although volumes are small. It should be noted that lignin already has very high end-use potential in for example battery materials, but there was insufficient information available for value added calculations. For the mechanical wood product industry, we anticipate that the proportion of further pro-cessed sawn timber products would increase relative to traditional sawn timber. This implies that emergence of a technologically advanced CLT and other wood product value-added ecosystem would emerge in Finland. For sawdust, a by-product from sawmilling, we assume it is used to produce carbohydrate-based emulsifiers, which have relatively high value, although volumes are small. Significant domestic value addition of bioproducts would require potentially tens of billions of euros of investment from industry. Despite national product development, industrial-scale production investments will not automatically be allocated to Finland. It is a “billion euro question” how Finland can become a more competitive and attractive destination for corporate investments. Companies base their investment decisions on their own criteria, but the public sector and the country’s industrial policy can influence these decisions. Is Finland an appealing enough for companies producing, for example textile fibers or other high value-added products? Do we have competitive industrial ecosystems that would encourage investments here? Advancing up the value chain would require investment in expertise enhancement, experimental environments, and scaling up. Success would also require increased R&D efforts, investments and renewed training. Automation and digitalization can be keys to improving productivity. Finland has the potential to significantly increase forest-based value added. There is hope, but the question remains: can we create a positive enough operating environment that both domestic and international companies are willing to invest in Finland?
Keywords: forest sector; bioeconomy; value chains